Human Development in The Works of HAMKA (International Journal of Academic Research in Progressive Education and Development, 2022)
Hamka was a well-known Muslim scholar, especially for the Malay Muslims of Southeast Asia. Even though Hamka’s scholarship is recognised by the intellectual community from Southeast Asia and the Middle East, he was also tainted with various accusations which contradicts his status as a scholar. Some of his writings were accused of being weak and does not have any value in human development. Therefore, this article tries to analyse the contents of Hamka’s philosophical work that are related to human development. The philosophical works are Tasawuf Moden, Falsafah Hidup, Lembaga Hidup and Lembaga Budi. The methods of data analysis carried out in this research are inductive and comparative methods. The research found that, when Hamka discusses the development of human beings, he emphasises the element of true faith and the amount of knowledge one possesses, both of these elements are primary elements in human development.
Keywords: Hamka, Human, Development, Philosophical Works, South East Asia